Cytomegalovirus-Specific CD4+ T-cell Responses and CMV-IgG Levels Are Associated With Neurocognitive Impairment in People Living With HIV. (1st September 2018) - Ballegaard, Vibe; Pedersen, Karin Kaereby; Pedersen, Maria; Brændstrup, Peter; Kirkby, Nikolai; Buus, Anette Stryhn; Ryder, Lars P.; Gerstoft, Jan; Nielsen, Susanne Dam
Abstract : Background: Mechanisms leading to neurocognitive impairment (NCI) in people living with HIV (PLWHIV) on stable combination antiretroviral therapy (cART) remain unknown. We investigated the association between immunity against cytomegalovirus (CMV), HIV-specific variables, and NCI in PLWHIV on stable cART and with low comorbidity. Methods: Fifty-two PLWHIV on stable cART and 31 HIV-uninfected controls matched on age, sex, education, and comorbidity were tested with a neurocognitive test battery, and CMV-immunoglobulin G (CMV-IgG) levels were measured. In PLWHIV, CMV-specific (CMV-pp65 and CMV-gB) CD4 + and CD8 + T-cell responses were measured using intracellular cytokine staining and flow cytometry. NCI was defined as a global deficit scale score (GDS score) ≥0.5. GDS scores and domain-specific scores defined severity of NCI. Logistic and linear multivariable regression analyses were used. Results: NCI was detected in 30.8% of PLWHIV, and HIV was associated with an adjusted odds ratio (aOR) of 5.18 [95% confidence interval (CI): 1.15 to 23.41, P = 0.033] for NCI. In PLWHIV, higher CMV-specific CD4 + T-cell responses increased the probability of NCI with an aOR of 1.68 (95% CI: 1.10 to 2.57) for CMV-pp65 or an aOR of 3.73 (95% CI: 1.61 to 16.98) for CMV-gB, respectively. Similar associations were not found with CMV-IgG or CMV-specific CD8 + T cells, but when assessing severity of NCI, higher CMV-IgG (per 100 U/mL) was associated with worse GDS scores (β = 0.08) (0.01–0.16), P = 0.044), specifically in the domain of speed of information processing (β = 0.20 (0.04–0.36, P = 0.019). Conclusions: PLWHIV had increased risk of NCI. Excess risk may be associated with CMV-specific CD4 + T-cell responses and CMV-IgG. Larger longitudinal studies investigating the impact of immunity against CMV on risk of NCI are warranted. Abstract : Supplemental Digital Content is Available in the Text.